Study on the architecture enhancement and migration for the next generation of the multimedia real time communication system - Yi JIANG; Yue ZHOU; Xueqian BAI; Bin WU; Chen LIU; Jianyin ZHANG (Dianxin kexue)
With the development of 5G and 5G-Advanced network, multimedia real time communications were migrating towards the trends of super high definition, enhanced interaction, immersion and openness, which requires enhancements on the architecture and capability of legacy IMS based multimedia real time communication system.The enhancement technologies of the multimedia real time communication system was studied and accordingly was proposed.By defining an“IMS network” based interactive data channel, a service-based unified media control architecture and procedures of third party identity on top of IMS network were proposed, to better fulfill the diverse and immersive service experiences for personal and vertical users.A new design of the real time communication system architecture was proposed, which enabled simpler, more flexible and more open mechanisms of the session control, session routing, media management, service invoking and combination.